2004
DOI: 10.1093/nar/gnh076
|View full text |Cite
|
Sign up to set email alerts
|

RNA stem-loop enhanced expression of previously non-expressible genes

Abstract: The key step in bacterial translation is formation of the pre-initiation complex. This requires initial contacts between mRNA, fMet-tRNA and the 30S subunit of the ribosome, steps that limit the initiation of translation. Here we report a method for improving translational initiation, which allows expression of several previously non-expressible genes. This method has potential applications in heterologous protein synthesis and high-throughput expression systems. We introduced a synthetic RNA stem±loop (stem l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…34 When stable hairpins where introduced in close proximity to the ribosome binding site of a highly expressed gfp-reporter construct, translation was drastically reduced. Positioning of the same hairpin outside of the TIR resulted in high expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 When stable hairpins where introduced in close proximity to the ribosome binding site of a highly expressed gfp-reporter construct, translation was drastically reduced. Positioning of the same hairpin outside of the TIR resulted in high expression.…”
Section: Resultsmentioning
confidence: 99%
“…This position does not interfere with ribosome binding as the contact region spans nucleotides -35 to +20 relative to the AUG. 35 It has been suggested that a stable hairpin prevents long range interaction of the TIR with the 3'-end of the corresponding mRNA. 34 It is possible that hairpins I and II of ROSE ibpA not only serve as a folding scaffold for hairpin III but also prevent the TIR from undesired downstream interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of mRNA secondary structure modification on bacterial translation, for instance, are studied in [56]. Inhibition of ribozymes by means of oligonucleotide directed RNA misfolding has been demonstrated e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Synthetic "modifier RNAs" have been used as experimental techniques for changing the gene expression patterns independent of the RNAi pathway 10,54,62 . One possible mechanism is the modification of (m)RNA structure as a consequence of the duplex formation between modifier and its target (m)RNA, which in turn can dramatically affect the binding affinity of the (m)RNA and a protein 25 .…”
Section: Regulation By Rnamentioning
confidence: 99%